Examining the Level of Career maturity among Foreign Asian Students by measuring Academic Level - Mustafa Tekke; Faiz Bin Adam Ghani (Intelektual Pustaka Media Utama, 2013)
The Asian individuals are dependent and collectivist compared with the western individuals that are independent and individualistic. Foreign Asian students choosing similar courses with their country friends do not reveal their career maturity and also lead to negative effect on their choices.Â This study aims at examining the level of career maturity of foreign Asian students in Malaysia based on academic level by using the Career Maturity Inventory. Two hundred and twenty nine ( Male=106, Female= 123) international students studying in various semesters completed the Career Maturity Inventory and it was reported that there were no significant differences between respondents of different academic semesters with regard to level of career maturity, this might reflect an educational level bias in the construction of the career decision-making. The findings of the current study are not consistent with theoretical expectations and prior research that international undergraduate senior students would be having higher career maturity than international undergraduate fresh students. Research emphasizes the reason behind might result from dependent and collectivist Asian culture that leading to fresh international students are higher career maturity compared to senior international students.